Case Report: Anthropometric profile and weight control strategies in a world boxing champion - Yáñez-Sepúlveda, Rodrigo; Herrera-Amante, Carlos Abraham; Carvajal-Veitía, Wiliam; Aarón Quiroga-Morales, Luis; Bonilla, Diego A.; Cortés-Roco, Guillermo; Aguilera-Martínez, Nicole; López-Gil, José Francisco (Frontiers in Sports and Active Living, 2025)
PurposeThis case study aims to examine the anthropometric profile and body composition management of a Mexican featherweight world champion during key preparatory periods leading up to the World Boxing Organization (WBO) title fight. Special emphasis is placed on the strategic role of nutritional periodization in achieving optimal body composition while preserving performance capacity in a body mass-restricted, high-performance setting.MethodsAnthropometric evaluations and octopolar bioelectrical impedance (BIA) measurements were conducted to assess body composition. The Heath and Carter somatotypes were calculated, complemented by proportionality analysis via the Phantom model of Ross and Wilson. Energy availability (EA) was estimated on the basis of fat-free mass (FFM) obtained via BIA, energy intake was recorded with the Automated Self-Administered 24-Hour (ASA24) Dietary Assessment Tool, and exercise energy expenditure was estimated through heart rate monitoring via the Hilloskorpi method.ResultsThe boxer presented low body fat levels (7.0% by BIA, sum of eight skinfolds = 45.0 mm) and high muscle mass percentages (53.1% by BIA and 46.6% by anthropometry). His somatotype was mesomorphic ectomorphic (1.5–2.8–5.2), with favorable body proportions, including a high relative span and ponderal index, alongside low cormic and adipose/muscular indices. Through nutritional periodization, a total body mass reduction of 6.85 kg was observed, including an acute loss of 5.35 kg (8.56%) during the final 10 days. Energy availability ranged from 35.7 kcal/kg FFM/day at the start of the preparation to 8.8 kcal/kg FFM/day in the final week before the fight.ConclusionThis case study highlights the relevance of regular monitoring of body composition through anthropometry and BIA assessment, combined with nutritional periodization, in supporting athlete preparation. Although very low energy availability was estimated during the final weeks, which should be carefully considered, the findings offer practical insights for body mass management strategies in elite boxing.